An ultra-high barrier EVOH aluminum-plated composite sheet and preparation method thereof

By plating aluminum on the EVOH film and modifying it to form a dense aluminum film and composite laminate structure, the shortcomings of the EVOH film in water barrier properties are solved, and its barrier properties are significantly improved. It is suitable for packaging materials in high humidity environments.

CN118752872BActive Publication Date: 2025-02-28REGO PACKING GZ IND CO LTD

Patent Information

Application Number
CN202411032020.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-30
Publication Date
2025-02-28
Estimated Expiration
2044-07-30

AI Technical Summary

Technical Problem

EVOH films are relatively weak in water-blocking properties and are prone to moisture absorption, affecting the overall barrier properties of packaging materials, especially in high humidity environments.

Method used

By plating aluminum on the EVOH film and modifying the EVOH with mica, quartz powder and feldspar powder, a dense aluminum film and composite laminate structure are formed to improve the density and barrier properties of the film.

Benefits of technology

It significantly improves the moisture-proof performance and overall barrier effect of EVOH film, enhances the barrier ability to water and oxygen, and extends the shelf life of packaging materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004970165260000091
    Figure BDA0004970165260000091
  • Figure BDA0004970165260000111
    Figure BDA0004970165260000111
  • Figure BDA0004970165260000121
    Figure BDA0004970165260000121
Patent Text Reader

Abstract

The present application relates to the field of ABL aluminum-plastic composite sheets, and more specifically, it relates to an ultra-high barrier EVOH aluminum-plated composite sheet and a preparation method thereof. An ultra-high barrier EVOH aluminum-plated composite sheet comprises an outer film, a first adhesive layer, a barrier layer, a second adhesive layer, and an inner film fixedly arranged in sequence; the barrier layer is made of an aluminum-plated EVOH film, the aluminum-plated EVOH film comprises an EVOH film layer and an aluminum layer covering the surface of the EVOH film layer, and the EVOH film layer is prepared from a modified EVOH material, and the modified EVOH material comprises the following components in terms of the mass percentage of the modified EVOH material: 2‑8% muscovite, 1‑5% quartz powder, 1‑5% feldspar powder, 0.1‑0.5% coupling agent, and EVOH supplements the remainder. The composite sheet of the present application has a significant barrier effect on water and oxygen, and has good mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of ABL aluminum-plastic composite sheets, and more specifically, to an ultra-high barrier EVOH aluminum-plated composite sheet and a preparation method thereof. Background Art

[0002] With the rapid development of the modern packaging industry, the barrier properties of packaging materials have become a key indicator for evaluating their performance. In the fields of food, medicine, daily chemicals, etc., packaging materials with good barrier properties can effectively prevent the adverse effects of external factors such as moisture and oxygen on products, thereby ensuring product safety, extending shelf life, and guaranteeing product quality.

[0003] At present, there are many packaging materials on the market that are widely used in various fields, among which EVOH (ethylene-vinyl alcohol copolymer) film has attracted much attention for its excellent oxygen barrier performance. EVOH film is a polymer material made of ethylene and vinyl alcohol copolymer. The vinyl group in its molecular structure gives it excellent mechanical properties and processing properties, while the vinyl alcohol group gives it excellent oxygen barrier properties. This unique molecular structure makes EVOH film have a wide range of application prospects in the packaging industry.

[0004] However, although EVOH film has excellent oxygen barrier properties, the hydroxyl groups in its molecular structure make it hydrophilic and hygroscopic. This property makes EVOH film relatively weak in water barrier performance and easy to absorb moisture. In areas with high barrier requirements, such as packaging of food, medicine, toothpaste and other products, the penetration and adsorption of moisture will affect the quality and shelf life of the product.

[0005] Therefore, how to overcome the shortcomings of EVOH film in water barrier performance and improve its overall barrier performance has become an urgent problem to be solved in the current packaging industry. Summary of the invention

[0006] In order to solve the above problems, the present application provides an ultra-high barrier EVOH aluminum-plated composite sheet and a preparation method thereof, wherein the composite sheet has a significant barrier effect on water and oxygen.

[0007] In the first aspect, the present application provides an ultra-high barrier EVOH aluminum-plated composite sheet, which adopts the following technical solution:

[0008] An ultra-high barrier EVOH aluminized composite sheet comprises an outer film, a first adhesive layer, a barrier layer, a second adhesive layer, and an inner film which are fixedly arranged in sequence; the barrier layer is made of an aluminized EVOH film, the aluminized EVOH film comprises an EVOH film layer and an aluminum layer covering the surface of the EVOH film layer, the EVOH film layer is prepared from a modified EVOH material, and the modified EVOH material comprises the following components, measured by mass percentage of the modified EVOH material: 2-8% muscovite, 1-5% quartz powder, 1-5% feldspar powder, 0.1-0.5% coupling agent, and the balance is supplemented by EVOH.

[0009] Aluminum is a metal with excellent barrier properties, especially in terms of oxygen, water vapor and ultraviolet light. By plating aluminum on the EVOH film, a dense aluminum film can be formed, forming a dense physical barrier, which effectively blocks the penetration of water vapor and prevents direct contact between water vapor molecules and the EVOH material, thereby reducing the hygroscopic properties of the EVOH film. At the same time, the aluminum layer has a reflective effect on water vapor molecules, which can reduce the adhesion and penetration of water vapor molecules on the surface of the film. The composite method of the present application can replace the traditional solution of using aluminum-plated PET film and EVOH film at the same time, saving materials and reducing costs.

[0010] The present application also modifies EVOH, and uses muscovite, quartz powder, and feldspar powder to form a composite laminated structure. Mica provides a natural barrier, and feldspar powder and quartz powder further improve the performance of the composite material through filling and reinforcement, which can effectively reduce the permeation channels in EVOH, making the penetration of gases, liquids and other substances more difficult. In the mixture of muscovite, quartz powder, and feldspar powder, some small particles of quartz powder and feldspar powder can fill the gaps between mica layers, reduce the agglomeration of particles in EVOH, and effectively improve the density of the EVOH film layer.

[0011] In addition, the special particles evenly dispersed in EVOH can enhance the roughness of the surface of the EVOH film layer, making its surface present tiny depressions or protrusions, so that the aluminum can adhere more firmly to the surface of the EVOH film layer and not fall off easily, thereby further improving the high barrier effect of the composite sheet.

[0012] Preferably, based on the mass percentage of the modified EVOH material, the modified EVOH material includes 4-8% muscovite, 1-3% quartz powder, 1-3% feldspar powder, 0.1-0.5% coupling agent, and EVOH makes up the balance.

[0013] By adopting the above technical solution, the dosage relationship of muscovite, quartz powder and feldspar powder in EVOH is further limited, the interaction between them is enhanced, and the various substances in the system have good interface compatibility, so that the modification effect is fully exerted.

[0014] Preferably, the particle size of the quartz powder is 15-30 nm, the particle size of the feldspar powder is 50-75 nm, and the specification of the muscovite mica is 200-400 mesh.

[0015] By adopting the above technical solution, the particle sizes of quartz powder, feldspar powder and muscovite are further limited. The specifications of quartz powder and feldspar powder are all at the nanometer level, which can enhance the interface effect with EVOH, better fill the tiny gaps in EVOH, effectively reduce the permeation channels of gas and liquid, and further improve its barrier performance.

[0016] Moreover, under this size limitation, quartz powder and feldspar powder can be more easily embedded into the layered structure of muscovite to form a new composite structure, which can alleviate the agglomeration effect of nano-scale particles to a certain extent.

[0017] Preferably, the preparation of the modified EVOH material comprises the following steps:

[0018] Step 1: dissolving a coupling agent, muscovite, quartz powder and feldspar powder in a solvent, stirring by ultrasonic, and then volatilizing the solvent to obtain mixed particles;

[0019] Step 2: Mix and extrude the mixed particles with EVOH to obtain modified EVOH material.

[0020] Preferably, the step 1 specifically includes the following operations:

[0021] Step 1a: dissolving the coupling agent in a solvent and stirring until uniform to obtain a mixed solvent;

[0022] Step 1b: adding quartz powder and feldspar powder to the mixed solvent, and stirring by ultrasonication; the ultrasonic power is 500-700W, and the ultrasonic time is 1-5min;

[0023] Step 1c: continue to add muscovite to the mixed solvent, and stir ultrasonically to obtain a mixture to be treated; the ultrasonic power is 1000-1200W, and the ultrasonic time is 10-15min;

[0024] Step 1d: volatilize the solvent in the mixture to be treated to obtain mixed particles.

[0025] By adopting the above technical solution and using a coupling agent to treat quartz powder, feldspar powder and muscovite mica, the surface free energy of the particles can be effectively reduced, making it difficult for the particles to agglomerate, and also achieving a better mixing effect between the mixed particles and EVOH.

[0026] Further limiting the ultrasonic power during mixing in step 1 can effectively promote more quartz powder and feldspar powder to be embedded in the laminated structure of muscovite to form a composite laminated structure, constitute a good barrier, and improve the mechanical properties of the EVOH film layer.

[0027] Preferably, the muscovite is treated at 600-700° C. for 15-45 minutes before being put into the solvent.

[0028] By adopting the above technical solution, the muscovite is subjected to a certain high-temperature treatment, so that its shape is changed, which is more conducive to the subsequent combination with quartz powder and feldspar powder.

[0029] Preferably, the EVOH is EVOH-32.

[0030] In actual research and development, EVOH-32 is selected as the basic raw material for modified EVOH material, which has a better coordination effect with quartz powder, feldspar powder, muscovite, etc. Moreover, EVOH-32 is widely used in packaging materials. This application conducts research and development on this raw material, which greatly amplifies the industrial value.

[0031] In the second aspect, the present application provides a method for preparing an ultra-high barrier EVOH aluminum-plated composite sheet, using the following technical solution:

[0032] A method for preparing an ultra-high barrier EVOH aluminum-plated composite sheet comprises the following steps:

[0033] Step A: Production of inner and outer films: After the polyethylene resin is melted, it is blown out to prepare the inner film and the outer film respectively for standby use;

[0034] Step B: Preparation of barrier layer:

[0035] Step B1: melting and blow-molding the modified EVOH material to obtain an EVOH film layer;

[0036] Step B2: using a vacuum aluminum plating process to deposit a uniform and dense aluminum layer on the surface of the EVOH film layer to form a barrier layer;

[0037] Step C: Composite molding: The inner film is bonded to one side of the barrier layer by a dry lamination or extrusion process to form a second bonding layer for connecting the inner film and the barrier layer; the other side of the barrier layer is bonded to the outer film by a dry lamination or extrusion process to form a first bonding layer for connecting the outer film and the barrier layer; and an ultra-high barrier EVOH aluminum-plated composite sheet is obtained.

[0038] By adopting the above technical solution, aluminum plating is performed on the EVOH film layer, which not only overcomes the defects of the EVOH film itself that it is easy to absorb moisture and has insufficient water barrier performance, but also significantly improves its barrier performance, especially water barrier performance. This improvement enables the EVOH aluminum-plated film composite sheet to maintain excellent barrier effect in a high humidity environment.

[0039] In addition, by introducing quartz powder, feldspar powder and muscovite mica, the present application can effectively improve the density and roughness of the EVOH film layer, which is beneficial for aluminum adhesion; at the same time, it also enhances the mechanical properties and stability of the film material, so that the composite sheet can still maintain excellent performance in complex environments.

[0040] This technology simplifies the structure and preparation process of the composite sheet and reduces the production cost. This improvement makes this technical solution more economical and feasible while maintaining high performance, providing the packaging industry with a new, high-performance, low-cost packaging material solution.

[0041] Preferably, the vacuum degree of the vacuum aluminum plating process is (1.4-1.6)×10 -2 Pa, the evaporation boat temperature is controlled at 1700-1800℃.

[0042] In summary, this application has the following beneficial effects:

[0043] 1. By aluminizing the EVOH film, a dense metal layer is formed, which effectively prevents the penetration and adsorption of moisture, thereby significantly improving the moisture-proof performance of the EVOH film. This improvement enables the EVOH aluminized film composite sheet to maintain excellent barrier effect in high humidity environments.

[0044] 2. In the present application, muscovite, quartz powder and feldspar powder are preferably used to modify EVOH, which can effectively reduce the permeation channels in EVOH, making the penetration of gases, liquids and other substances more difficult, and effectively improving the water and gas barrier properties of the modified EVOH material.

[0045] 3. The special combination of muscovite, quartz powder and feldspar powder in the present application can effectively improve the agglomeration phenomenon between particles and disperse them evenly in EVOH, thereby increasing the density of the EVOH film layer and improving the mechanical properties of the EVOH film layer. DETAILED DESCRIPTION

[0046] The present application is further described in detail below with reference to the embodiments.

[0047] The raw materials used in the following examples and comparative examples are all commercially available products.

[0048] Example

[0049] Example 1

[0050] An ultra-high barrier EVOH aluminum-plated composite sheet comprises an outer film, a first adhesive layer, a barrier layer, a second adhesive layer, and an inner film which are fixedly arranged in sequence. The first adhesive layer and the second adhesive layer play the role of bonding and connection, and are specifically dry composite glue purchased from Bostik, with the brand names of bostik H108 and bostik LF518. The outer film and the inner film are formed by blowing polyethylene after melting in a film blowing machine, and the polyethylene is commercially available. The specific model of polyethylene used for the inner film of this embodiment is PE3505, purchased from ExxonMobil; the specific models of polyethylene used for the outer film are PE3505 and HTA108, purchased from ExxonMobil, and the mass ratio of PE3505 and HTA108 is 1:1.

[0051] The material of the barrier layer is an aluminized EVOH film, and the aluminized EVOH film comprises an EVOH film layer and an aluminum layer covering the surface of the EVOH film layer.

[0052] The EVOH film layer is prepared from modified EVOH material, and the modified EVOH material is composed of muscovite, quartz powder, feldspar powder, coupling agent and EVOH-32.

[0053] The quartz powder is commercially available and in this embodiment was purchased from Shijiazhuang Borui Building Materials Co., Ltd. The purchased quartz powder was dried and ground into 25 nm.

[0054] Feldspar powder is commercially available, specifically potassium feldspar powder, which in this embodiment is purchased from Shijiazhuang Oumeiya Mineral Products Co., Ltd. The purchased feldspar powder is dried and ground into 60 nm.

[0055] Muscovite is commercially available and was purchased from Yaoyang Mineral Products Processing Plant in Lingshou County in this embodiment. The purchased muscovite was calcined in a muffle furnace at 650° C. for 30 min, passed through a 300-mesh sieve, and set aside.

[0056] The coupling agent is a silane coupling agent, specifically KH550, which is commercially available.

[0057] EVOH-32 is commercially available and has an ethylene molar content of 32%. In this embodiment, it was purchased from Sinopec Sichuan Wei Chemical Company and its model number is EW-3201.

[0058] The specific content of each raw material is shown in Table 1.

[0059] The preparation of the modified EVOH material comprises the following steps:

[0060] Step 1: preparing mixed particles, comprising the following steps:

[0061] Step 1a: Dissolve the coupling agent in a solvent (acetone solution), stir until uniform, and obtain a mixed solvent.

[0062] Step 1b: adding quartz powder and feldspar powder to the mixed solvent, and stirring by ultrasonic method; the ultrasonic power is 600 W, and the ultrasonic time is 3 min.

[0063] Step 1c: continue to add muscovite to the mixed solvent and stir it ultrasonically to obtain a mixture to be treated; the ultrasonic power is 1100 W and the ultrasonic time is 12 min.

[0064] Step 1d: placing the mixture to be treated in hot air at 60° C. to evaporate the solvent and obtain mixed particles.

[0065] Step 2: Put the mixed particles and EVOH into a twin-screw compounding extruder, melt-mix and discharge the mixture to obtain modified EVOH material.

[0066] The conditions for compounding and extrusion were as follows: temperature from the feeding section to the die section: 175°C, 190°C, 190°C, 185°C, main engine speed 100r / min, and feeding speed 15r / min.

[0067] The present application also provides a method for preparing an ultra-high barrier EVOH aluminum-plated composite sheet, comprising the following steps: Step A: Production of inner and outer films: After the polyethylene resin is melted, it is blown out separately to prepare an inner film and an outer film for standby use.

[0068] Specifically, polyethylene particles are added to the extruder, and after being melted, they are extruded from the annular gap of the front port die into a cylindrical (tube) shape, and compressed air is introduced from the center hole of the core rod of the die head to blow the cylinder into a bubble tube shape (generally blown up 2-3 times). At this time, there is elongation in both the vertical and horizontal directions to obtain an inflated bubble tube, which is cooled by an outer air ring, and then enters the guide clamping plate and the traction clamping roller to flatten the bubble tube to prevent the air in the bubble tube from leaking out to maintain the required constant blowing pressure. The flattened bubble tube becomes a flat-folded double-layer film to obtain an inner film / outer film for standby use.

[0069] During inner film production, the temperature settings of each zone are as follows: Zone 1 155±5℃, Zone 2 185±5℃, Zone 3 185±5℃, Zone 4 195±5℃.

[0070] During outer film production, the temperature settings of each zone are as follows: Zone 1 155±5℃, Zone 2 185±5℃, Zone 3 185±5℃, Zone 4 195±5℃.

[0071] Step B: Preparation of barrier layer:

[0072] Step B1: The modified EVOH material is put into an extruder, melted at 185° C., and then blow-molded to obtain an EVOH film layer.

[0073] Step B2: Vacuum-coat the EVOH film layer on a vacuum aluminum coating machine, and deposit a uniform and dense aluminum layer on the surface of the EVOH film layer to form a barrier layer as a whole. The vacuum degree is 1.5×10-2 Pa, the evaporation boat temperature is controlled at 1750°C, the purity of the aluminum wire is not less than 99.99%, the wire feeding speed is 2m / min, the winding speed is 60m / min; the thickness of the aluminum layer is 400 angstroms.

[0074] Step C: Composite molding: The inner film is bonded to one side of the barrier layer by a dry lamination process to form a second bonding layer for connecting the inner film and the barrier layer; the other side of the barrier layer is bonded to the outer film by a dry lamination process to form a first bonding layer for connecting the outer film and the barrier layer; and an ultra-high barrier EVOH aluminum-plated composite sheet is obtained.

[0075] Specifically, dry lamination glue is coated on the surface of the inner film, and dried in an oven at 80°C to dry out all the solvent in the dry lamination glue, and the dry lamination glue is melted under heating, and then the barrier layer is laminated thereto, and the dry lamination process is completed after cooling and aging treatment; at this time, the dry lamination glue becomes the second adhesive layer.

[0076] The other side of the barrier layer is coated with dry glue, which is dried in an oven at 80°C to completely dry out the solvent in the dry glue. The dry glue is melted under heating, and the outer film is bonded to it. After cooling and aging, the dry glue process is completed; at this time, the dry glue becomes the first adhesive layer.

[0077] Example 2

[0078] An ultra-high barrier EVOH aluminum-plated composite sheet comprises an outer film, a first adhesive layer, a barrier layer, a second adhesive layer, and an inner film which are fixedly arranged in sequence. The first adhesive layer and the second adhesive layer play the role of bonding and connection, and are specifically dry composite glue purchased from Bostik, with the brand names of bostik H108 and bostik LF518. The outer film and the inner film are formed by blowing polyethylene after melting in a film blowing machine, and the polyethylene is commercially available. The specific model of polyethylene used for the inner film of this embodiment is PE3505, purchased from ExxonMobil; the specific models of polyethylene used for the outer film are PE3505 and HTA108, purchased from ExxonMobil, and the mass ratio of PE3505 and HTA108 is 1:1.

[0079] The material of the barrier layer is an aluminized EVOH film, and the aluminized EVOH film comprises an EVOH film layer and an aluminum layer covering the surface of the EVOH film layer.

[0080] The EVOH film layer is prepared from modified EVOH material, and the modified EVOH material is composed of muscovite, quartz powder, feldspar powder, coupling agent and EVOH-32.

[0081] The quartz powder is commercially available and in this embodiment was purchased from Shijiazhuang Borui Building Materials Co., Ltd. The purchased quartz powder was dried and ground into 15 nm.

[0082] Feldspar powder is commercially available, specifically potassium feldspar powder, which in this embodiment was purchased from Shijiazhuang Oumeiya Mineral Products Co., Ltd. The purchased feldspar powder was dried and ground into 50 nm.

[0083] Muscovite is commercially available and was purchased from Yaoyang Mineral Products Processing Plant in Lingshou County in this embodiment. The purchased muscovite was calcined in a muffle furnace at 600° C. for 45 min, passed through a 200-mesh sieve, and set aside.

[0084] The coupling agent is a silane coupling agent, specifically KH550, which is commercially available.

[0085] EVOH-32 is commercially available and has an ethylene molar content of 32%. In this embodiment, it was purchased from Sinopec Sichuan Wei Chemical Company and its model number is EW-3201.

[0086] The specific content of each raw material is shown in Table 1.

[0087] The preparation of the modified EVOH material comprises the following steps:

[0088] Step 1: preparing mixed particles, comprising the following steps:

[0089] Step 1a: Dissolve the coupling agent in a solvent (acetone solution), stir until uniform, and obtain a mixed solvent.

[0090] Step 1b: Add quartz powder and feldspar powder to the mixed solvent and stir by ultrasonication; the ultrasonic power is 500 W and the ultrasonic time is 5 min.

[0091] Step 1c: continue to add muscovite to the mixed solvent and stir it ultrasonically to obtain a mixture to be treated; the ultrasonic power is 1000 W and the ultrasonic time is 15 min.

[0092] Step 1d: placing the mixture to be treated in hot air at 60° C. to evaporate the solvent and obtain mixed particles.

[0093] Step 2: Put the mixed particles and EVOH into a twin-screw compounding extruder, melt-mix and discharge the mixture to obtain modified EVOH material.

[0094] The conditions for compounding and extrusion were as follows: temperature from the feeding section to the die section: 175°C, 190°C, 190°C, 185°C, main engine speed 100r / min, and feeding speed 15r / min.

[0095] A method for preparing an ultra-high barrier EVOH aluminum-plated composite sheet, which is different from that of Example 1 in that: in step B2, the vacuum degree is 1.4×10 -2 Pa, the evaporation boat temperature was controlled at 1800°C.

[0096] Example 3

[0097] An ultra-high barrier EVOH aluminum-plated composite sheet comprises an outer film, a first adhesive layer, a barrier layer, a second adhesive layer, and an inner film which are fixedly arranged in sequence. The first adhesive layer and the second adhesive layer play the role of bonding and connection, and are specifically dry composite glue purchased from Bostik, with the brand names of bostik H108 and bostik LF518. The outer film and the inner film are formed by blowing polyethylene after melting in a film blowing machine, and the polyethylene is commercially available. The specific model of polyethylene used for the inner film of this embodiment is PE3505, purchased from ExxonMobil; the specific models of polyethylene used for the outer film are PE3505 and HTA108, purchased from ExxonMobil, and the mass ratio of PE3505 and HTA108 is 1:1.

[0098] The material of the barrier layer is an aluminized EVOH film, and the aluminized EVOH film comprises an EVOH film layer and an aluminum layer covering the surface of the EVOH film layer.

[0099] The EVOH film layer is prepared from modified EVOH material, and the modified EVOH material is composed of muscovite, quartz powder, feldspar powder, coupling agent and EVOH-32.

[0100] The quartz powder is commercially available and in this embodiment was purchased from Shijiazhuang Borui Building Materials Co., Ltd. The purchased quartz powder was dried and ground into 30 nm.

[0101] Feldspar powder is commercially available, specifically potassium feldspar powder, which in this embodiment was purchased from Shijiazhuang Oumeiya Mineral Products Co., Ltd. The purchased feldspar powder was dried and ground into 75 nm.

[0102] Muscovite is commercially available and was purchased from Yaoyang Mineral Products Processing Plant in Lingshou County in this embodiment. The purchased muscovite was calcined in a muffle furnace at 700° C. for 15 min, passed through a 400-mesh sieve, and set aside.

[0103] The coupling agent is a silane coupling agent, specifically KH550, which is commercially available.

[0104] EVOH-32 is commercially available and has an ethylene molar content of 32%. In this embodiment, it was purchased from Sinopec Sichuan Wei Chemical Company and its model number is EW-3201.

[0105] The specific content of each raw material is shown in Table 1.

[0106] The preparation of the modified EVOH material comprises the following steps:

[0107] Step 1: preparing mixed particles, comprising the following steps:

[0108] Step 1a: Dissolve the coupling agent in a solvent (acetone solution), stir until uniform, and obtain a mixed solvent.

[0109] Step 1b: adding quartz powder and feldspar powder to the mixed solvent, and stirring by ultrasonic method; the ultrasonic power is 700 W, and the ultrasonic time is 1 min.

[0110] Step 1c: continue to add muscovite to the mixed solvent and stir it ultrasonically to obtain a mixture to be treated; the ultrasonic power is 1200 W and the ultrasonic time is 10 min.

[0111] Step 1d: placing the mixture to be treated in hot air at 60° C. to evaporate the solvent and obtain mixed particles.

[0112] Step 2: Put the mixed particles and EVOH into a twin-screw compounding extruder, melt-mix and discharge the mixture to obtain modified EVOH material.

[0113] The conditions for compounding and extrusion were as follows: temperature from the feeding section to the die section: 175°C, 190°C, 190°C, 185°C, main engine speed 100r / min, and feeding speed 15r / min.

[0114] A method for preparing an ultra-high barrier EVOH aluminum-plated composite sheet, which is different from that of Example 1 in that: in step B2, the vacuum degree is 1.6×10 -2 Pa, the evaporation boat temperature was controlled at 1700°C.

[0115] Example 4

[0116] An ultra-high barrier EVOH aluminum-plated composite sheet is different from Example 1 in that the specific contents of the raw materials of the modified EVOH material are different, see Table 1 for details.

[0117] A method for preparing an ultra-high barrier EVOH aluminum-plated composite sheet is the same as that in Example 1 and will not be described in detail here.

[0118] Table 1

[0119]

[0120] Example 5

[0121] An ultra-high barrier EVOH aluminum-plated composite sheet, which is different from Example 1 in that:

[0122] Quartz powder is commercially available, and in this embodiment, it was purchased from Shijiazhuang Borui Building Materials Co., Ltd. The purchased quartz powder was dried and ground through a 300-mesh sieve.

[0123] Feldspar powder is commercially available, specifically potassium feldspar powder, which in this embodiment is purchased from Shijiazhuang Oumeiya Mineral Products Co., Ltd. The purchased feldspar powder is dried and ground to pass through a 300-mesh sieve.

[0124] Muscovite is commercially available and was purchased from Yaoyang Mineral Products Processing Plant in Lingshou County in this embodiment. The purchased muscovite was calcined in a muffle furnace at 650° C. for 30 min, ground to 20 nm, and set aside.

[0125] A method for preparing an ultra-high barrier EVOH aluminum-plated composite sheet is the same as that in Example 1 and will not be described in detail here.

[0126] Example 6

[0127] An ultra-high barrier EVOH aluminum-plated composite sheet, which is different from Example 1 in that:

[0128] Muscovite is commercially available and was purchased from Yaoyang Mineral Products Processing Plant in Lingshou County in this embodiment. The purchased muscovite was sieved through a 300-mesh sieve for later use.

[0129] A method for preparing an ultra-high barrier EVOH aluminum-plated composite sheet is the same as that in Example 1 and will not be described in detail here.

[0130] Example 7

[0131] An ultra-high barrier EVOH aluminum-plated composite sheet, which is different from Example 1 in that:

[0132] The preparation of modified EVOH material includes the following steps:

[0133] Step 1: preparing mixed particles, comprising the following steps:

[0134] Step 1a: Dissolve the coupling agent in a solvent (acetone solution), stir until uniform, and obtain a mixed solvent.

[0135] Step 1b: adding quartz powder and feldspar powder to the mixed solvent, and stirring by ultrasonic method; the ultrasonic power is 600 W, and the ultrasonic time is 3 min.

[0136] Step 1c: continue to add muscovite to the mixed solvent and stir it ultrasonically to obtain a mixture to be treated; the ultrasonic power is 1600 W and the ultrasonic time is 12 min.

[0137] Step 1d: placing the mixture to be treated in hot air at 60° C. to evaporate the solvent and obtain mixed particles.

[0138] Step 2: Put the mixed particles and EVOH into a twin-screw compounding extruder, melt-mix and discharge the mixture to obtain modified EVOH material.

[0139] The conditions for compounding and extrusion were as follows: temperature from the feeding section to the die section: 175°C, 190°C, 190°C, 185°C, main engine speed 100r / min, and feeding speed 15r / min.

[0140] A method for preparing an ultra-high barrier EVOH aluminum-plated composite sheet is the same as that in Example 1 and will not be described in detail here.

[0141] Comparative Example

[0142] Comparative Example 1

[0143] An ultra-high barrier EVOH aluminum-plated composite sheet, which is different from Example 1 in that the aluminum layer is omitted.

[0144] A method for preparing an ultra-high barrier EVOH aluminum-plated composite sheet is different from that of Example 1 in that step B2 is omitted accordingly.

[0145] Comparative Example 2

[0146] An ultra-high barrier EVOH aluminum-plated composite sheet is different from Example 1 in that the muscovite in the modified EVOH material is replaced by silicon dioxide.

[0147] A method for preparing an ultra-high barrier EVOH aluminum-plated composite sheet is the same as that in Example 1 and will not be described in detail here.

[0148] Comparative Example 3

[0149] An ultra-high barrier EVOH aluminum-plated composite sheet material, which is different from Example 1 in that the quartz powder in the modified EVOH material is replaced with heavy calcium powder.

[0150] A method for preparing an ultra-high barrier EVOH aluminum-plated composite sheet is the same as that in Example 1 and will not be described in detail here.

[0151] Comparative Example 4

[0152] An ultra-high barrier EVOH aluminum-plated composite sheet is different from Example 1 in that the feldspar powder in the modified EVOH material is replaced by talcum powder.

[0153] A method for preparing an ultra-high barrier EVOH aluminum-plated composite sheet is the same as that in Example 1 and will not be described in detail here.

[0154] Comparative Example 5

[0155] An ultra-high barrier EVOH aluminum-plated composite sheet is different from Example 1 in that the modified EVOH material contains 1% muscovite, 9.5% quartz powder and 0.5% feldspar powder.

[0156] A method for preparing an ultra-high barrier EVOH aluminum-plated composite sheet is the same as that in Example 1 and will not be described in detail here.

[0157] Performance testing

[0158] 1. Water barrier test: According to YBB00092003-2015 "Water Vapor Transmission Rate Determination Method", the ultra-high barrier EVOH aluminum-plated composite sheets of Examples 1-7 and Comparative Examples 1-5 were tested, and the water vapor transmission rates were recorded in Table 2.

[0159] 2. Gas barrier test: According to GB / T 1038-2000 "Plastic film and sheet gas permeability test method pressure difference method", the ultra-high barrier EVOH aluminum-plated composite sheets of Examples 1-7 and Comparative Examples 1-5 were tested, and the oxygen permeation was recorded in Table 2.

[0160] 3. Mechanical properties: The EVOH film layers of Examples 1-7 and Comparative Examples 2-5 were tested with reference to GB / T 1040 “Determination of tensile properties of plastics”, and the tensile strengths were recorded in Table 3.

[0161] Table 2

[0162]

[0163]

[0164] According to the data in Table 2, the ultra-high barrier EVOH aluminum-plated composite sheets of Examples 1-7 have good barrier effects on water vapor and oxygen, and the permeation rate is relatively low.

[0165] Comparative Example 1 is based on Example 1, but the aluminum layer is omitted. The hydrophilicity and hygroscopicity of the EVOH film layer made of the modified EVOH material are improved. Even if the aluminum layer is omitted, the barrier effect to water vapor is equivalent to that to oxygen. However, due to the lack of the physical barrier of the aluminum layer, the overall barrier property is still inferior to that of Example 1.

[0166] Comparative Examples 2-4 are based on Example 1, but any of the muscovite, quartz powder, and feldspar powder is replaced with other raw materials. The performance of the modified EVOH material obtained cannot be effectively improved, and the coordination effect between the EVOH film layer and the aluminum layer cannot be fully exerted. Therefore, even with the aluminum layer as a physical barrier, the barrier performance of the composite sheet of Comparative Examples 2-4 is still not as good as that of Example 1, especially the barrier effect against water vapor. This is because, firstly, after the special coordination is destroyed, the hydrophilic and hygroscopic properties of the EVOH film layer itself cannot be fully and effectively improved; secondly, it may also affect the surface roughness of the EVOH film layer, and the coordination between the EVOH film layer and the aluminum layer is not as tight and dense as that of Example 1, resulting in poor barrier performance of the composite sheet of Comparative Examples 2-4.

[0167] Comparative Example 5 is based on Example 1, but the special dosage of muscovite, quartz powder and feldspar powder in the system is destroyed, so that the performance of the modified EVOH material cannot be effectively improved. Therefore, Comparative Example 5 also shows inferior barrier properties to Example 1.

[0168] This shows that there is some special combination between muscovite, quartz powder, feldspar powder and EVOH, which can effectively improve the performance of EVOH, enhance its own water barrier and gas barrier effects, and cooperate well with the aluminum layer, so that the composite sheet exhibits excellent barrier effect.

[0169] Example 5 is based on Example 1, but the particle size relationship of muscovite, quartz powder and feldspar powder is not within the optimal matching relationship; Example 6 is based on Example 1, but the calcination treatment of muscovite is omitted, so that the muscovite is not in the optimal matching form; Example 7 is based on Example 1, but the ultrasonic power of the muscovite, quartz powder and feldspar powder is increased. The above changes have more or less affected the matching of muscovite, quartz powder and feldspar powder in the system. Although the special matching can be carried out, it does not occur under the optimal conditions, resulting in a decrease in barrier performance.

[0170] This indicates that if the specifications and mixing conditions of muscovite, quartz powder and feldspar powder can be further limited, the modification effect on EVOH can be better exerted.

[0171] Table 3

[0172]

[0173]

[0174] According to the data in Table 3, the EVOH film layer prepared by the modified EVOH material of Examples 1-7 has better tensile strength and excellent mechanical properties than that of Comparative Examples 2-5. The tensile strength has roughly the same performance trend as the water barrier and gas barrier performance tests, indicating that the combination of muscovite, quartz powder and feldspar powder in the system can greatly improve the performance of EVOH and simultaneously improve the mechanical and barrier effects of EVOH.

[0175] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. An ultra-high barrier EVOH aluminum-plated composite sheet, characterized in that: It includes an outer film, a first adhesive layer, a barrier layer, a second adhesive layer, and an inner film which are fixedly arranged in sequence; the barrier layer is made of an aluminized EVOH film, the aluminized EVOH film includes an EVOH film layer and an aluminum layer covering the surface of the EVOH film layer, the EVOH film layer is prepared from a modified EVOH material, and the modified EVOH material includes the following components in terms of mass percentage: 2-8% muscovite, 1-5% quartz powder, 1-5% feldspar powder, 0.1-0.5% coupling agent, and the balance is supplemented by EVOH; The particle size of the quartz powder is 15-30nm, the particle size of the feldspar powder is 50-75nm, and the specification of the muscovite is 200-400 mesh; The preparation of the modified EVOH material comprises the following steps: Step 1: dissolving a coupling agent, muscovite, quartz powder and feldspar powder in a solvent, stirring by ultrasonic, and then volatilizing the solvent to obtain mixed particles; The step 1 specifically includes the following operations: Step 1a: dissolving the coupling agent in a solvent and stirring until uniform to obtain a mixed solvent; Step 1b: adding quartz powder and feldspar powder to the mixed solvent, and stirring by ultrasonication; the ultrasonic power is 500-700W, and the ultrasonic time is 1-5min; Step 1c: continue to add muscovite to the mixed solvent, and stir ultrasonically to obtain a mixture to be treated; the ultrasonic power is 1000-1200W, and the ultrasonic time is 10-15min; Step 1d: volatilizing the solvent in the mixture to be treated to obtain mixed particles; Step 2: Mixing and extruding the mixed particles with EVOH to obtain modified EVOH material; The muscovite needs to be treated at 600-700° C. for 15-45 minutes before being put into the solvent.

2. The ultra-high barrier EVOH aluminized composite sheet according to claim 1, characterized in that: Calculated by mass percentage of the modified EVOH material, the modified EVOH material includes 4-8% muscovite, 1-3% quartz powder, 1-3% feldspar powder, 0.1-0.5% coupling agent, and EVOH supplements the balance.

3. The ultra-high barrier EVOH aluminum-plated composite sheet according to claim 1, characterized in that: The EVOH is EVOH-32.

4. A method for preparing the ultra-high barrier EVOH aluminum-plated composite sheet according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step A: Production of inner and outer films: After the polyethylene resin is melted, it is blown out to prepare the inner film and the outer film respectively for standby use; Step B: Preparation of barrier layer: Step B1: melting and blow-molding the modified EVOH material to obtain an EVOH film layer; Step B2: using a vacuum aluminum plating process to deposit a uniform and dense aluminum layer on the surface of the EVOH film layer to form a barrier layer; Step C: Composite molding: The inner film is bonded to one side of the barrier layer by a dry lamination or extrusion process to form a second bonding layer for connecting the inner film and the barrier layer; the other side of the barrier layer is bonded to the outer film by a dry lamination or extrusion process to form a first bonding layer for connecting the outer film and the barrier layer; and an ultra-high barrier EVOH aluminum-plated composite sheet is obtained.

5. The method for preparing the ultra-high barrier EVOH aluminum-plated composite sheet according to claim 4, characterized in that: The vacuum degree of the vacuum aluminum plating process is (1.4-1.6)×10 -2 Pa, the evaporation boat temperature is controlled at 1700-1800℃.

Citation Information

Patent Citations

  • Preparation method of spraying heat insulation mica tape

    CN116968402A

  • High-barrier white BOPP aluminum laminated film

    CN211968714U

Cited By

  • EVOH high-barrier film for ensiling bag and preparation method of EVOH high-barrier film

    CN120792274A

  • EvoH high-barrier film for silage bag and method for manufacturing the same

    CN120792274B